Effects of varying secondary channel widths on flow boiling heat transfer and pressure characteristics in oblique-finned microchannels. (October 2016) - Law, Matthew; Lee, Poh-Seng
Highlights: Heat transfer performance deteriorates with larger secondary channel widths. Larger secondary channels promote slug agglomeration from neighbouring microchannels. Sustained thin-film evaporation is completely absent from larger secondary channels. Pressure drop sustained in larger secondary channel geometries are greater. 0.15-mm secondary channel demonstrates higher degree of flow boiling stability. Abstract: The oblique-finned structure has been proven to exhibit significant enhancements in heat transfer in both single-phase and two-phase modes of operation coupled with slight increment in pressure drop. These enhancements come with the mitigation of two-phase flow instability compared to the conventional straight-finned microchannels, which encourages further parametric studies on the fin geometry. In the present work, flow boiling experiments are conducted in oblique-finned microchannels using the FC-72 dielectric fluid with varying secondary channel widths to investigate its effects on two-phase heat transfer, pressure drop and flow boiling instabilities. Three different secondary channel widths of 0.15 mm, 0.30 mm and 0.45 mm are tested with mass fluxes ranging from 197 kg/m 2  s to 394 kg/m 2  s, and effective heat fluxes from 14.9 W/cm 2 to 70.2 W/cm 2 with the aid of high-speed visualisations. From the experiments and flow visualisations, it is found that increasing the width of the secondary channels has adverse effect on heat transfer performance and critical heat flux limit due to the inability of the microchannels to suppress flow boiling instabilities. Pressure drop penalty of the larger secondary channel configurations are higher as a result of greater amount of flow diversion, which amplifies flow migration from the draining edge to the filling edge of the oblique-finned array.